The Agreement of a Two- and a Three-Dimensional Speckle-Tracking Global Longitudinal Strain - Plášek, Jiří; Rychlý, Tomáš; Drieniková, Diana; Cisovský, Ondřej; Grézl, Tomáš; Homza, Miroslav; Václavík, Jan (Journal of clinical medicine, 2022)
BACKGROUND: Two-dimensional (2D) and three-dimensional (3D) speckle-tracking echocardiography (STE) enables assessment of myocardial function. Here, we examined the agreement between 2D and 3D STE measurement of a global longitudinal strain (GLS) in patients with normal left ventricle, reduced ejection fraction, and cardiac pacing. METHODS: Our analysis included 90 consecutive patients (59% males; average age: 73.2 ± 11.2 years) examined between May 2019-December 2020, with valid 2D and 3D loops for further speckle-tracking strain analysis. Linear regression, Pearson correlation, and a Bland-Altman plot were used to quantify the association between 2D and 3D GLS and related segments, using the 17-segment American Heart Association (AHA) model. Analyses were performed in the entire study group and subgroups. Intra- and inter-observer variability of 2D and 3D GLS measurement was also performed in all participants. RESULTS: We observed a strong correlation between 2D and 3D GLS measurements (R = 0.76, p < 0.001), which was higher in males (R = 0.78, p < 0.001) than females (R = 0.69, p < 0.001). Associated segment correlation was poor (R = 0.2-0.5, p < 0.01). The correlation between 2D and 3D GLS was weaker in individuals with ventricular pacing of >50% (R = 0.62, p < 0.001) than <50% (R = 0.8, p < 0.001), and in patients with LVEF of <35% (R = 0.69, p = 0.002) than >35% (R = 0.72, p < 0.001). Intra-observer variability for 2D and 3D GLS was 2 and 2.3%, respectively. Inter-observer variability for 2D and 3D GLS was 3.8 and 3.6%, respectively Conclusion: Overall 2D and 3D GLS were closely associated but not when analyzed per segment. It seems that GLS comparison is more representative of global shortening than local displacement. Right ventricular pacing and reduced left ventricular ejection fraction were associated with a reduced correlation between 2D and 3D GLS.